Prevalence and determinants of academic bullying among medical and dental students in Jordan - Hana Taha; Omar Alshadaidah; Salwa Samhouri; Malek Awamleh; Hana Hadidi; Suhib Awamleh; Martin Söderberg; Vanja Berggren; Linus Jönsson (Frontiers in Health Services, 2026)
Background Academic bullying is a well-recognized issue in medical education, carrying considerable consequences for mental health, academic performance, and even patient care. The issue remains understated, as most victims refrain from reporting due to fear of repercussions. This is especially relevant in the MENA region, where data on the topic is already sparse. This study aims to report the prevalence, types, associated factors, and perceived effects of academic bullying among medical and dental students at a Jordanian university. Methods A cross-sectional study collected the data from 383 medical and dental students at a public Jordanian university, using a self-administered questionnaire assessing sociodemographic, bullying involvement, types, determinants and responses. Depressive and anxiety symptoms were measured using the PHQ-9 and GAD-7. Victims and non-victims were compared using the Mann–Whitney U and chi-square tests; binary logistic regression identified independent predictors of victimization. Results Of the 383 participants, 38.6% reported some involvement in bullying: 27.7% as witnesses only, 4.2% as victims only, and 6.8% as both victims and witnesses. Verbal bullying was the most prevalent form in both the witnessed and victimized groups (69.7% and 73.8%, respectively), with fellow students being the most commonly reported perpetrators. Independent predictors of victimization included a history of childhood bullying (OR = 12.05, 95% CI: 4.88–37.0) and lower GPA (OR = 0.38, 95% CI: 0.18–0.79) Conclusion Academic bullying remains prevalent yet underreported among Jordanian medical and dental students, with measurable consequences for mental health and academic life. Certain groups — particularly those with a childhood bullying history —appear more vulnerable to victimization. These findings support the need for accessible, confidential reporting systems, routine mental health screening, and peer-support programs in medical education.